Economic Analysis of Innovative Methods and Their Implementation in The Food and Pharmaceutical Industry - Milan MAJERNÍK; Stefan MAJERNIK (Communications of International Proceedings, 2022)
The development of innovative food and pharmaceutical processing technologies, the Draft Criteria for Integrated Prevention, follows on from the Decision of the European Parliament and of the Council concerning the Seventh Framework Program of the European Community for research, technological development and demonstration activities. In the last three decades, a number of polysaccharides and polysaccharide-protein complexes have been isolated from fungi, mainly focusing on the isolation of glucans used as therapeutic agents. The most promising pharmacological effects of these biopolymers are their immunomodulatory ability, anti-cancer effects. On the basis of innovative methods and innovative technologies to work on basic research into the method of isolation of beta glucan from the oyster mushroom Pleurotus ostreatus. You will gain the acquired knowledge and know-how in your own unique method of isolation, which will allow you to obtain beta glucan in a purity of up to 93%. S economically analyze the results of applied innovative methods and innovative technologies.
Keywords: Innovative Technologies; Food Industry; Pharmaceutical Industry; Mushrooms; Oyster Mushrooms; Polysaccharides; Glucans; Economic Results